PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA TOKO PRIMA VARIASI KOTA BENGKULU - Widya Panca Putri; Adi Sismanto (UM. Bengkulu, 2020)
This study aims to determine how much the influence of Service Quality and Product Quality on Consumer Satisfaction in the Variety Prima Store Bengkulu City. This research uses quantitative research methods. The population in this study were 180 Prima Variasi Store consumers and sampling using the Total Sampling method. Based on the results of multiple linear regression obtained by the regression equation Y = 7,352 + 0.195 (X1) + 0.240 (X2). The results of the study and the hypothesis show that Service Quality (sig Î± = 0,000 <0.050), Product Quality (sig Î± = 0.018 <0.050). Simultaneously significant effect on Consumer Satisfaction. Partially, both Service Quality and Product Quality variables have a significant influence on Consumer Satisfaction. Keywords: Service Quality, Product Quality, Consumer Satisfaction.